Theoretical investigation on solid solution effect in dilute Zr alloys: Insight into mechanical and thermal properties - D. Wang; Z. Xie; B.D. Yao; J.X. Si; L. Wu; X.Y. Wu; Y.X. Wang (Journal of Materials Research and Technology, 2024)
Solid solution effect of minor elements on mechanical and especially thermal properties of zirconium (Zr) alloys has been underexplored in previous studies. This research delves into the electronic structure, phonon, mechanics, and thermodynamics of binary solid solution Zr alloys (introduction of Sn, Cu, Al, Ge, O, N, H, and C) using density functional theory (DFT). Micro-mechanical properties are changed after doping elements, particularly for doping H as interstitials. The H-induced increase in Poisson's ratio and decrease in shear modulus, Young's modulus, and hardness should be due to H-induced enhancement in the ductility of adjacent Zr atoms. Addition-induced thermodynamic properties are discernible for substitutional and interstitial elements. High frequencies of phonons appear in the Zr alloys with interstitial solid solution, which decreases the heat capacity of the Zr alloys. Conversely, the alloys featuring a substitutional solid solution experience negligible changes in heat capacity. Grüneisen parameter associated with anharmonic interaction is a determining factor in the thermal expansion of the Zr alloys. In low phonon frequencies (≤2 THz), the more negative contribution of Grüneisen parameter leads to the lower thermal expansion of the Zr alloys with interstitial solid solution, with respect to substitutional solid solution. Deep investigation reveals that the mode of lattice vibration in the low frequency almost remains the original transverse mode of the pure Zr for interstitial solid solution. For substitutional solid solution, the atomic layer containing doping element vibrates from transversely to longitudinally. Our work helps purposefully tune the properties of novel Zr alloys through screening and adding alloying elements.